An experimental study on the effect of visual tasks on discomfort due to peripheral glare - Kent, Michael G.; Fotios, S.; Altomonte, Sergio (Taylor & Francis, 2018)
This article concerns discomfort due to sources of glare in the peripheral visual field. A visual task is needed to maintain foveal fixation at a known location and in past studies the tasks have ranged from a simple fixation mark to a task requiring greater cognitive attention such as reading. It was hypothesized that these different approaches to control visual attention would influence the evaluation of discomfort. This article reports an experiment which compared evaluations of discomfort when using the two visual tasks, a simple circle and a pseudo-text reading task, and two procedures, category rating and luminance adjustment. The results from both procedures confirmed the hypothesis: a lower degree of discomfort was expressed in the pseudo-text trials than in trials with the circular fixation mark.